Comparative efficacy of different dietary interventions for cardiopulmonary fitness at high altitude: a systematic review and network meta-analysis - Wang, Bin; Xiong, Yanle; Lin, Ning; Shi, Jiaojiao; Zou, Bo; Ma, Xin; Zeng, Kaihong; Kang, Chao (Frontiers in Nutrition, 2025)
BackgroundA plateau hypoxic environment can increase the physiological burden on athletes. Although nutritional interventions have been recognized as a potential strategy to improve plateau acclimatization, evidence in support of specific dietary patterns is still lacking. This study compared the effects of different dietary interventions on cardiopulmonary fitness during plateau exercise through systematic evaluation and network meta-analysis methods.MethodsThis study systematically reviewed relevant literature up to June 2025 and included 20 randomized controlled trials (RCTs) conducted at altitudes above 1,500 meters involving healthy participants aged 16 years and above who engaged in physical activities. The primary outcomes included cardiopulmonary indicators [maximal oxygen uptake (VO2max), heart rate (HR)], blood biomarkers [peripheral oxygen saturation (SpO2), hematocrit (HCT)], and subjective perception indicators [rating of perceived exertion (RPE)]. For each outcome, the pooled effects of each intervention compared to others were estimated. Mean difference (MD) or standardized mean difference (SMD) with 95% Credible Intervals (95% CrI) were calculated. The Surface Under the Cumulative Ranking Curve (SUCRA) was used to rank the dietary interventions and quantify their relative effectiveness. In addition, the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach was applied to assess the quality of evidence.ResultsA total of 20 randomized controlled trials involving 329 participants were included, evaluating eight dietary interventions. Moderate-quality evidence indicated that carbohydrate supplementation significantly improved the percentage of maximal oxygen uptake (VO2max) compared to placebo (SMD = 1.13, 95% CrI: 0.25 to 2.05) and reduced RPE scores (MD = −0.77, 95% CrI: −1.83 to −0.09). Moderate-quality evidence indicated that carbohydrate supplementation combined with glutamine ranked highest in improving SpO2 (SUCRA 84.54%) and RPE (SUCRA 69.37%), while iron supplementation showed the highest SUCRA rankings for HR (56.54%) and HCT (66.67%). However, these interventions did not demonstrate statistically significant advantages. Notably, the observed increase in VO2max exceeded the minimally clinically important difference (MCID) of 1.0 ml/kg/min reported in previous studies, suggesting that the effect of carbohydrate supplementation on VO2max may have clinical relevance.ConclusionsDifferences exist in the effects of different dietary interventions on cardiopulmonary fitness during altitude exercise. The current network meta-analysis indicates that carbohydrate-based strategies show beneficial effects, with carbohydrate plus glutamine supplementation demonstrating greater advantages in SpO2 and RPE, while carbohydrate alone is more supported in improving VO2max. Therefore, carbohydrate-based strategies may serve as effective options to promote altitude acclimatization, whereas iron supplementation may have potential benefits in improving HCT and HR.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD420251069629, identifier: CRD420251069629.